1970
DOI: 10.1172/jci106412
|View full text |Cite
|
Sign up to set email alerts
|

Male pseudohermaphroditism due to 17α-hydroxylase deficiency

Abstract: A B STRA CT This is the first report of a male with 17a-hydroxylase deficiency resulting in male pseudohermaphroditism, ambiguous external genitalia, absence of male secondary sexual characteristics, and gynecomastia at puberty. Diagnosis was based on extensive studies of steroid metabolism including the following: low urinary excretion of 17-ketosteroids and 17-hydroxycorticoids which did not increase after ACTH; no response of very low plasma testosterone and dehydroepiandrosterone to adrenocorticotropin (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
2
3

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(76 citation statements)
references
References 23 publications
3
68
2
3
Order By: Relevance
“…Expression studies of this particular type of compound heterozygote are now under way. Although in most cases of this disorder increased production of DOC in the zona fasciculata results in suppression of both PRA and aldosterone production in zona glomerulosa [5,6], the aldosterone level was not suppressed in the present case. Similar findings have also been reported in this disorder particularly from Japan [3], but the exact mechanisms of this aldosterone production are still unknown.…”
contrasting
confidence: 54%
“…Expression studies of this particular type of compound heterozygote are now under way. Although in most cases of this disorder increased production of DOC in the zona fasciculata results in suppression of both PRA and aldosterone production in zona glomerulosa [5,6], the aldosterone level was not suppressed in the present case. Similar findings have also been reported in this disorder particularly from Japan [3], but the exact mechanisms of this aldosterone production are still unknown.…”
contrasting
confidence: 54%
“…Initially, it was thought that such patients had a concomitant deficiency in 18-OH-dehydrogenase in the adrenal glands. However, Goldsmith et al, (1967) and New and Suvannakul (1970) have indicated that the mechanism might be due to sodium retention; the expansion of the extracellular volume suppresses the renin-angiotensin system and thereby inhibits the 18-OHdehydrogenase in the adrenal glands. Currently, the latter mechanism is believed to be more likely (Levine & New, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Very often P450c17 deficiency remains undiagnosed until adolescence or early adulthood: overproduction of corticosterone substitutes for low cortisol production and prevents an adrenal crisis. Cortisol impairment results in secondary ACTH oversecretion and adrenal stimulation to produce large amounts of DOC which leads to clinical manifestations of mineralocorticoid excess: increased renal tubular resorption of sodium and kaliuresis, producing hypertension, hypokalemia and suppressed plasma renin activity (6). Thus, the adrenal zona glomerulosa does not receive renin stimulation for aldosterone synthesis, resulting in reduced aldosterone secretion (7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the impaired production of sex steroids leads to abnormal sexual development. Therefore, this deficiency is clinically characterized by hypertension, hypokalemia, and sexual abnormalities such as 46,XY disorder of sex development (DSD) or sexual infantilism in 46,XX females (3)(4)(5)(6).…”
mentioning
confidence: 99%